IMPROVING JOB SATISFACTION THROUGH EMPLOYEE SOCIAL SECURITY AND COMPENSATION - Riesca Anindya Septantina; Maulida Lintang Ayu Kinanti; Nurmala Noviolita; Basyiruddin Basyiruddin (Sekolah tinggi ilmu ekonomi pemuda, 2026)
This study aims to analyze the effect of social security and compensation on increasing employee job satisfaction in the Semen Indonesia Foundation environment. The method used in this study is quantitative with a quantitative experimental approach used to determine the effect of independent variables of social security and compensation on increasing employee job satisfaction. The population consists of all 22 employees, who are also sampled through a total sampling technique. Data collection uses a questionnaire with a five-point Likert scale, while data analysis uses Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that social security has a positive and significant effect on increasing employee job satisfaction with a path coefficient of 0.524 and a p-value of 0.000<0,05, and has a large category effect. Compensation also has a positive and significant effect on increasing employee job satisfaction with a path coefficient of 0.376 and a p-value of 0.007<0,05 with a medium category. Simultaneously, both variables are able to explain 68% of the variation in increasing employee job satisfaction. The conclusion of this study confirms that employee social security and compensation are important factors in increasing employee job satisfaction, and therefore, organizations should prioritize them when formulating human resource welfare policies.